Tragic Form in Kamila Shamsie's Home Fire. (10th September 2021) - Weiss, Naomi
Abstract: This article examines Kamila Shamsie's adaptation of Sophocles' Antigone in Home Fire (2017), a novel focused on Muslim identity, Islamophobia, and citizenship rights in contemporary Britain. It demonstrates that this novel is a multimedia work full of theatrical traces: a literary archive that preserves the dramatic quality of Sophocles' play but also encompasses multiple other forms of media and performance, from theatre and television to social media. The article focuses not so much on how Shamsie has adapted the plot of Antigone but on her reworking of tragedy's formal features or structures, such as dialogue, the chorus, and the messenger speech. In this polyphonic novel, such multimedia theatricality facilitates something that Greek tragedy itself produces: a contestation of multiple voices for audiences to hear, critique, and put against their own. Shamsie's manipulation of tragic form thus contributes to Home Fire 's political import.